Control of Luminescence by Tuning of Crystal Symmetry and Local Structure in Mn4+‐Activated Narrow Band Fluoride Phosphors. Issue 7 (17th January 2018) - Fang, Mu‐Huai; Wu, Wei‐Lun; Jin, Ye; Lesniewski, Tadeusz; Mahlik, Sebastian; Grinberg, Marek; Brik, Mikhail G.; Srivastava, Alok M.; Chiang, Chang‐Yang; Zhou, Wuzong; Jeong, Donghyuk; Kim, Sun Hee; et al.
Abstract: Mn 4+ ‐doped fluoride phosphors have been widely used in wide‐gamut backlighting devices because of their extremely narrow emission band. Solid solutions of Na2 (Si x Ge1− x )F6 :Mn 4+ and Na2 (Ge y Ti1−y )F6 :Mn 4+ were successfully synthesized to elucidate the behavior of the zero‐phonon line (ZPL) in different structures. The ratio between ZPL and the highest emission intensity υ6 phonon sideband exhibits a strong relationship with luminescent decay rate. First‐principles calculations are conducted to model the variation in the structural and electronic properties of the prepared solid solutions as a function of the composition. To compensate for the limitations of the Rietveld refinement, electron paramagnetic resonance and high‐resolution steady‐state emission spectra are used to confirm the diverse local environment for Mn 4+ in the structure. Finally, the spectral luminous efficacy of radiation (LER) is used to reveal the important role of ZPL in practical applications. Abstract : Solid solutions of Na2 (Si x Ge1− x )F6 :Mn 4+ and Na2 (Ge y Ti1− y )F6 :Mn 4+ were successfully synthesized by the co‐precipitation method to elucidate the behavior of the zero‐phonon line (ZPL) owing to its high sensitivity to the local coordinated environment. The control of the ZPL is examined from the view of structure, electronic, and optical properties. All show promise in the practical application of white‐light diodes.